Jonathan Edwards and the life of God : toward an evangelical theology of participation - Hastings, W. Ross (Minneapolis, MN : Fortress Press, 2015)
Jonathan Edwards and the Life of God aims to offer a retrieval of Edwards's theology of participation for contemporary evangelical theology. It critically expounds and elucidates the concept of participation in God, or theosis, in Edwards's Trinitarian theology as it relates to around three unions: the three persons of the Trinity, the hypostatic union of the divine and human in Christ, and that of believers with Christ. This volume brings Edwards's rich theological work into conversation with the patristic (Augustine and the Cappadocians) and Reformed traditions (Calvin and, especially, Barth), in order to construct with Edwards a more hopeful, liberating, and truly human version of Christian life. Consideration of the life of God in Edwards thus moves "beyond" in two senses: first, perspectives on participation beyond those of Edwards from Barth, Volf, the Cappadocian Fathers, and others in the tradition, are engaged in order to locate and critique and enhance it; and secondly, in the sense that, as Hastings argues, participation leads, for Edwards and others, into the "beyond" of the beatific vision--the glory of God, which is the hope that, amongst other things, motivates the Christian life
Acknowledgements -- Chronology of the primary works of Edwards -- Introduction -- A journey of participation -- A journey into the union of the Trinity -- A journey yet deeper into the union of the Trinity -- A journey into the bond of the trinity : the spirit in the Trinity -- Journey from heaven to earth : the spirit honored in the incarnation of Christ -- Journey of human participation in God : the spirit honored in the union of the saints with God -- Participation in the spirit in justification for sanctification or for sanctification and justification? -- Journey with assurance? : the spirit honored in the assurance of salvation in believers -- Journey of contemplative, communal intimacy towards becoming fully human persons in Christ.
Includes bibliographical references (pages 471-501) and indexes.
Print version record.
JSTOR
Keywords: Edwards, Jonathan, -- 1703-1758 -- Criticism and interpretation; Edwards, Jonathan, -- 1703-1758; Mystical union; Union mystique; RELIGION -- Christian Theology -- History; RELIGION -- Christianity -- Presbyterian; Mystical union; Criticism, interpretation, etc